Evaluating the On-Street Bicycle Lane and Bicyclist Safety in Malaysia - A. Roslan; N.S. Mohd Zulkiffli; H. Mohamed Jamil; N.Z. Harun; N. Jamaluddin; R. Hamidun; N.F. Rahmat; A.S. Mohd Yusof; K.A. Abu Kassim (Journal of the Society of Automotive Engineers Malaysia, 2022)
Cycling is getting a trend as one of the physical activities in Malaysia. In line with that, the government introduced a morning car-free day and enhanced bicyclist facilities, especially in the residential area in 2014. Though facilities like bicycle lanes are provided, bicyclists do not use them. This study was designed to observe and analyze bicyclist perceptions of the underutilization of bicycle facilities. Two types of data collection were conducted; (i) observation at five (5) selected on-street bicycle lanes in Klang Valley, and (ii) online survey (n=520, and out of this 85% were bicyclists). The observation found that only 7% of bicyclists cycle in the residential area during the study period. Meanwhile, the study also found the sharing path between the motorway and bicycle lane may increase the number of misuses (motorized parked or driving through the bicycle lane) which in turn reflects the utilization rate of the bicycle lane. Bicyclist safety continues the main obstacle to promoting bicycle lanes in Malaysia. The bicyclist denies the drivers always giving way and priority to them.